Pelatihan Pembuatan Sabun dan Strategi Digitalisasi Pemasaran sebagai Upaya Pemberdayaan Ekonomi: Penelitian - Jimatul Arrobi; Ulfatu Solihah; Ilham Abdullah Azam; Siti Nuryu Aidah; Putri Nurdiana (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Village economic empowerment is a national development priority to reduce inequality and improve welfare and independence. This study aims to analyze the effectiveness of the implementation of a soap-making training program and digital marketing strategies as an effort to empower the economy in Karangjaya Village. This study used a descriptive qualitative approach. The research subjects were PKK members and mothers. The results showed that this program was able to increase community capacity in aspects of production, packaging, and marketing skills. The expected impact of this program is the creation of new business units, an increase in the average income of participants, and increased self-confidence in entrepreneurship. This program demonstrates that the combination of technical skills with digital literacy can be a powerful catalyst in achieving economic independence at the village level.